Kesejahteraan Subjektif Ditinjau dari Virtue Transcendence dan Coping Stress - Nurul Faqih (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
This study aims to determine the effect of virtue transcendence and coping stress variables on subjective well-being of young students in Indramayu. A sample of 424 adolescents were taken from three Islamic boarding schools in Indramayu, the technique of taking data using simple random sampling. Measuring instruments used to measure subjective well-being in this study are the FS (Flourishing Scale) and SPANE (Scale of Positive and Negative Affect) developed by Diener & Diener (2009), the measuring instrument used to measure virtue transcendence is VIA- The IS (Values in Action Inventory of Strengths) developed by Peterson & Seligman (2004), and the measuring tool for measuring coping stress is the ways of coping developed by Lazarus and Folkman (1984) in the form of self reports. The major hypothesis test results from this study are that there is a significant effect of virtue transcendence and coping stress on subjective well-being with a value of R2; 0.361 (36.1%) and p-value; 0,000.